Hypertension and correlates among Montenegrin schoolchildren—a cross-sectional study. (June 2017) - Martinovic, M.; Belojevic, G.; Evans, G.W.; Kavaric, N.; Asanin, B.; Pantovic, S.; Jaksic, M.; Boljevic, J.
Abstract: Objectives: In one of the few national studies of children in a former Eastern bloc country emerging as a Western democracy and the first such study ever in Montenegro, this study establishes the prevalence and correlates of childhood hypertension (CH). Study design: A cross-sectional national study. Methods: The study was conducted with 3254 children aged 7–13 years (50.3% male) from 39 elementary schools. We used a structured questionnaire to gather sociodemographic information as well as data on factors potentially related to CH. Children's nutritional status was assessed using the criteria of the International Obesity Task Force. Waist circumference was also measured. Blood pressure was measured in schools using an oscillometric monitor. CH was defined as an average systolic blood pressure and/or diastolic blood pressure greater than or equal to the 95th percentile for sex, age, and height. Results: The prevalence of CH was 10.4% with no differences between boys and girls. Multiple regression revealed that the odds for child hypertension were lowered by 10% for each year of age. On the other hand, rural environment and child obesity raised the odds of hypertension by 38% and 68%, respectively. Conclusions: We found hypertension in one out of ten Montenegrin schoolchildren, with no gender differences. Obesity and rural areas may be unfriendly to children's blood pressure. Highlights: We show that the prevalence of hypertension in Montenegrin schoolchildren is 10.4%, with no gender differences. The prevalence of childhood hypertension decreases with age. Obesity and rural environment may be unfriendly to children's blood pressure.